HIPNOTERAPI SEBAGAI PENDEKATAN BARU PENDIDIKAN ISLAM - Indana, Nurul (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
Hypnosis and Hypnotherapy in the past few years have provoked tremendous interest. The airing of hypnosis shows on various television stations makes the public understand that hypnosis creates an incorrect perception, that humans are helpless humans who can be so easily influenced and tricked by others. In the event that you're looking for the best way to get the most out of your own home, you've got come to the right place. In this research, there are two focuses, namely: the concept of Hypnotherapy, the concept of hypnotherapy in the perspective of Islamic education. While the purpose of this research are: To know the concept of hypnotherapy, to know the concept of hypnotherapy in the perspective of Islamic education. The method used in this research is library research. The approach used in this research is normative and psychological approach. Normative means that the research takes its basis from the original source, namely Al-Qur'an and Al-Hadith. Psychology means that this research studies a person's soul through behavioural symptoms that can be observed. Hypnotherapy in the perspective of Islamic Education is one of the healing methods that uses psychological aspects that study the benefits of suggestion to overcome problems, thoughts, feelings and behaviours that are applied in the scope of Islamic education that is guided by the Al-Quran and Al-Hadith.